2018
DOI: 10.1186/s12864-018-5237-1
|View full text |Cite
|
Sign up to set email alerts
|

Gene ontology analysis of expanded porcine blastocysts from gilts fed organic or inorganic selenium combined with pyridoxine

Abstract: BackgroundGene ontology analysis using the microarray database generated in a previous study by this laboratory was used to further evaluate how maternal dietary supplementation with pyridoxine combined with different sources of selenium (Se) affected global gene expression of expanded porcine blastocysts. Data were generated from 18 gilts randomly assigned to one of three experimental diets (n = 6 per treatment): i) basal diet without supplemental Se or pyridoxine (CONT); ii) CONT + 0.3 mg/kg of Na-selenite a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…and that high antioxidant levels may help improve embryo quality, the only sensible conclusion is that embryos do synthesize antioxidant enzymes themselves even in in vitro conditions that may avoid some of the physiological mechanisms for maternal selenium transfer regulation. Therefore, we tend to believe that the effects of selenium on embryo development are mainly due to the effects on genomic stability, intracellular ceramides synthesis, and peptides trafficking (as concluded in [52]), rather than because of all antioxidant activity. In fact, in the article [53], it has been shown that in vivo other complementary antioxidant mechanisms were upregulated by selenium supplementation, but not the GPX system.…”
Section: Discussionmentioning
confidence: 99%
“…and that high antioxidant levels may help improve embryo quality, the only sensible conclusion is that embryos do synthesize antioxidant enzymes themselves even in in vitro conditions that may avoid some of the physiological mechanisms for maternal selenium transfer regulation. Therefore, we tend to believe that the effects of selenium on embryo development are mainly due to the effects on genomic stability, intracellular ceramides synthesis, and peptides trafficking (as concluded in [52]), rather than because of all antioxidant activity. In fact, in the article [53], it has been shown that in vivo other complementary antioxidant mechanisms were upregulated by selenium supplementation, but not the GPX system.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that regardless of the source of maternal dietary Se, Se content in embryos would come from an organic metabolite: either from SeMet pool of oocytes and/or oocyte selenoproteins [47]. Therefore, it can be hypothesized that oocyte (maternal) selenoproteins provide a common source of SeCys for embryo selenoprotein synthesis [47].…”
Section: Se Effect On In Vitro Embryo Developmental Potentialmentioning
confidence: 99%
“…It has also been suggested that regardless of the source of maternal dietary Se, Se content in embryos would come from an organic metabolite: either from SeMet pool of oocytes and/or oocyte selenoproteins [47]. Therefore, it can be hypothesized that oocyte (maternal) selenoproteins provide a common source of SeCys for embryo selenoprotein synthesis [47]. Interestingly, this hypothesis is partly supported by the findings of two recent studies, where higher Se level and GPX activities were observed in embryos harvested from Se-supplemented gilts, reinforcing the notion that embryos, regardless of maternal dietary Se source, may obtain their Se content from a common intermediary Se metabolite [83,84].…”
Section: Se Effect On In Vitro Embryo Developmental Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Sec needs to be broken down by the specific enzyme selenocysteine lyase (Scly) into l -alanine and HSe − (SeMet → Sec → HSe − ) [ 69 71 ]. Historically, more attention has been paid to the effect of vitamin B6 on the catalyzation in the Scly step [ 72 76 ] rather than the essential role of serine [ 77 ].…”
Section: The Transformation Of Serine Into Selenocysteine Through a Trna-dependent Pathwaymentioning
confidence: 99%